Suicide among the elderly: what are Brazilian publications about? (Research, Society and Development, 2020)
The study aims to characterize national scientific publications on suicide among the elderly, through an integrative literature review. The searches were carried out in the databases of the Scientific Eletronic Library Online (SCIELO), Latin American Literature in Health Sciences (LILACS) and Medical Literature Analyzes and Retrieval System Online (MEDLINE), considering the period from January 2000 to June 2020 , using the expression: (suicide OR “suicidal ideation” OR “suicide attempt”) AND (elderly OR seniors OR aging OR old age). 248 articles were found, of which 24 studies met the selection criteria, of these 29% of the publications (n ​​= 7) were published in 2012. In general, the studies use the epidemiological method and psychological or psychosocial autopsies, investigating risk factors related to the phenomenon. It is noticed that there is a complexity of biopsychosocial factors that permeate suicide, and it is essential to develop public policies that focus on the mental health of the elderly.